Participative social work and urban change: two case studies in Lisbon and Bucharest - Cordeiro, Graça Índias; Florea, I.; Figueiredo, T. (Sociologia On Line, 2011)
Focusing on two initiatives working within disadvantaged urban neighborhoods in Bucharest and Lisbon, we want to discuss the civil society’s capacity to adapt to the changing social opportunities and difficul-ties, and its ability to create equal access to resources and opportunities. We propose to compare some aspects of both initiatives in these two historical and socio-political Southern European urban contexts, trying to better understand these processes: what they manage to do; what they find hard to do; who helps them; their relationships with different state structures (municipality, schools, national agencies etc.); their relationships with different people in the area of work; their future perspective, and so on. Our diverse social activist and academic background in anthropological, sociological, geographical fields allows us to a deeper understanding of the strengths and limits of theoretical and practical dimensions of social research process, witch we would like to discuss, also.